The Effects of Brand Strategy and Design Innovation on the Brand Performance of the Malaysian Furniture Firms -- UTM Thesis KIV - Tamyez, Puteri Fadzline (2014)
Brand strategy and design innovation is frequently discussed as key sources of competitive advantage and subsequent brand performance, particularly in the context of SMEs and large sized firms. One of the sectors that are affected by the growth of branding and design innovation is the furniture manufacturing sector. However, there is a concern of whether the manufacturers are fully equipped with branding strategy and design innovation. This ambiguity comes largely from determinants of brand performance in the SME context that have received only limited research attention. This research addresses this issue. Therefore, the main objective of this study is to examine the effects of brand strategy and design innovation on the brand performance of the Malaysian furniture firms. More specifically, this research empirically examines (1) The influence of brand barriers on brand orientation (2) The influence of brand orientation towards brand distinctiveness (3) The relationship between brand orientation and brand performance (4) The relationship between brand distinctiveness and brand performance (5) The influence of brand distinctiveness on design innovation (6) The relationship between design innovation and its dimensions (7) The effect of design innovation on brand performance (8) brand distinctiveness as a mediator between brand orientation and brand performance (9) design innovation as a mediator between brand distinctiveness and brand performance, along with twelve hypotheses. Primary data were collected for a sample size of 269 firms in Malaysia for empirical verification using AMOS Structural Equation Modelling. The data collection was conducted over a two-month period from CEOs and marketing managers in the furniture manufacturing companies. The survey response rate resulted to 37.5 percent. The analysis of the structural model reveals all twelve hypotheses are significant including seven positive paths, three negative paths and two mediators. Overall there are four direct paths towards brand performance which are brand barriers, design innovation, brand orientation and brand distinctiveness. Two additional paths are found significant in the SEM model along with two mediators. Academically, these empirical sights fill the gaps of literature on the relationships between these factors affecting the brand performance of the furniture industry. It also provides insights into what are the key design innovations that contribute to the brand performance of the furniture firms. This will further enable firms to self-check their branding strategy and design innovation to enhance their performance in the market. Thus, policy makers in the furniture industry should give more priority in redesigning their brand strategy and design innovation to further improve and sustain their brand performance in the furniture sector.